Computational investigations of indanedione and indanone derivatives in drug discovery: Indanone derivatives inhibits cereblon, an E3 ubiquitin ligase component. (December 2022) - Nayek, Upendra; Basheer Ahamed, Syed Ibrahim; Mansoor Hussain, Ummul Halilunnisa; Unnikrishnan, Mazhuvancherry Kesavan; Abdul Salam, Abdul Ajees
Abstract: Background: Cereblon, an extensively studied multifunctional protein, is a Cullin 4-RING E3 ubiquitin ligase complex component. Cereblon is a well-known target of thalidomide and its derivatives. Cereblon is involved in multiple myeloma cell apoptosis. When ligands such as thalidomide and lenalidomide bind to cereblon, it recognizes various neosubstrates based on the ligand shape and properties. We have identified novel CRBN inhibitors, namely DHFO and its analogs, with structural features that are slightly different from thalidomide but stronger cereblon-binding affinity. We selected indanedione and indanone derivatives from the literature to understand and compare their cereblon-mediated substrate recognition potential. Methods: Computational investigations of possible CRBN inhibitors were investigated by molecular docking with Autodock Vina and DockThor programs. The properties of the compounds' ADME/T and drug-likeness were investigated. A molecular dynamics study was carried out for four selected molecules, and the molecular interactions were analyzed using PCA-based FEL methods. The binding affinity was calculated using the MM/PBSA method. Results: We conducted computational investigations on 68 indanedione and indanone derivatives binding with cereblon. Ten molecules showed better CRBN binding affinity than thalidomide. We studied the drug-likeness properties of the selected ten molecules, and four of the most promising molecules (DHFO, THOH, DIMS, and DTIN) were chosen for molecular dynamics studies. The MM/PBSA calculations showed that the DHFO, already shown to be a 5-LOX/COX2 inhibitor, has the highest binding affinity of − 163.16 kJ/mol with cereblon. Conclusion: The selected CRBN inhibitor DHFO has demonstrated the highest binding affinity with cereblon protein compared to other molecules. Thalidomide and its derivatives have a new substitute in the form of DHFO, which produces an interaction hotspot on the surface of the cereblon. Ease of chemical synthesis, low toxicity, versatile therapeutic options, and pleiotropism of DHFO analogs provide an opportunity for exploring clinical alternatives with versatile therapeutic potential for a new category of indanedione molecules as novel modulators of E3 ubiquitin ligases. Graphical Abstract: Computational studies of CRBN with indanedione and indanone derivatives ga1 Highlights: The human cereblon is a multifunctional protein, and its expression is associated with the proliferation of tumor cells. Cereblon is the direct target of immunosuppressive medications such as lenalidomide employed in multiple myeloma. Here we present a number of novel indanedione and indanone derivatives with high binding affinity to cereblon. This paper covers computational investigations between human cereblon protein and indanedione/indanone derivatives. In silico predictions imply a high-affinity binding between cereblon and the indanone molecule DHFO.